PENINGKATAN HASIL BELAJAR MELALUI DINAMIKA KELOMPOK DALAM PERKULIAHAN PENGAJARAN PSIKOLOGI DAN BIMBINGAN KONSELING (PPBK) - Indah Sukmawati; Neviyarni Neviyarni; Yarmis Syukur; Asrul Said (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2013)
This research is divided in three cycles, aiming to make learning outcomes students participating in college increased to more optimally. Based on the results of a pretest and posttest, describe the utilization of group dynamics in PPBK studies can improve the quality of student learning outcomes. While the value of acquired skills related to student devised of Rencana Pelaksanaan Layanan Bimbingan Konseling (RPLBK) in accordance with the specific KIPD and showing the skills of learning is increased.This research result suggest: that the activities of the utilization of group dynamics can be done in a variety of learning to help students hold the material and do exercise either in an individual or classical group; develop the habit of learning groups that utilize the dynamics that develop in it can make students more active, vibrant and creative learning; other lecturers may try to carry out the study group which utilizes the dynamics that develop within the group to improve the quality of studies at college.